2021
DOI: 10.1007/s10584-021-03054-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of climate change on agro-climatic indicators in the UK

Abstract: The effect of climate change on agriculture in the UK is here assessed using a comprehensive series of policy-relevant agro-climate indicators characterising changes to climate resources and hazards affecting productivity and operations. This paper presents projections of these indicators across the UK with gridded observed data and UKCP18 climate projections representing a range of greenhouse gas emissions scenarios. The projections can be used to inform climate change mitigation and adaptation policy. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 39 publications
0
22
0
1
Order By: Relevance
“…Further, prolonged heat is also an important indicator of crop heat stress (Arnell and Freeman, 2021); figures produced using max_maxT give very similar patterns to max_meanT (not shown).…”
Section: Association Between Climate Extremes and Wheat Yields In Each Crop Growth Stagementioning
confidence: 85%
See 1 more Smart Citation
“…Further, prolonged heat is also an important indicator of crop heat stress (Arnell and Freeman, 2021); figures produced using max_maxT give very similar patterns to max_meanT (not shown).…”
Section: Association Between Climate Extremes and Wheat Yields In Each Crop Growth Stagementioning
confidence: 85%
“…However, the anomalous years (e.g. 1976 and 2013) suggest that this can occur, and recent research indicates that days exceeding heat stress temperatures for wheat are likely to increase under climate change (Arnell et al, 2021). The increase in high temperatures and their variability is evident in the Production phase across the three regions (max_maxT and var_maxT, Figure 7).…”
Section: Seasonal Projections Of Future Crop-growing Conditionsmentioning
confidence: 94%
“…Previous studies found divergence in trends of drought characteristics between SPI and SPEI in observations (Stagge et al, 2017;Karimi et al, 2020;Ionita and Nagavciuc, 2021), historical climate simulations (Chiang et al, 2021) and future climate projections (e.g. Arnell and Freeman, 2021;García-Valdecasas Ojeda et al, 2021;Wang et al, 2021;Ogunrinde et al, 2021), with SPEI indicating increased drying compared to SPI. Increases in PET under a changing climate, combined with the high sensitivity of SPEI to PET changes, cause amplified projections of climatological drying and even a reversal of wetting trends in some parts of the world compared to when only changes in precipitation are considered (Cook et al, 2014).…”
Section: Differences Between Spi and Spei Projectionsmentioning
confidence: 95%
“…Increases in PET under a changing climate, combined with the high sensitivity of SPEI to PET changes, cause amplified projections of climatological drying and even a reversal of wetting trends in some parts of the world compared to when only changes in precipitation are considered (Cook et al, 2014). For the UK, Arnell and Freeman (2021) found that projected increases in drought frequency based on SPEI6 exceeded those based on SPI3, which is attributed to the inclusion of the effect of PET in SPEI, although the aggregation period difference likely amplified this effect. By applying the delta method using UKCP18 probabilistic projections, Arnell and Freeman (2021) with opposite signs (increasing for SPEI, decreasing for SPI).…”
Section: Differences Between Spi and Spei Projectionsmentioning
confidence: 99%
See 1 more Smart Citation